Nursing education in India: a boon for the global healthcare system - N., Sushma; Nadagaddi, Satish B.; Madhusheela, S.; Begum, Shaik M.; Priya, S. Chetan; Shenbega Priya, J. Sathya; N., Geethanjali (International Journal Of Community Medicine And Public Health, 2025)
Nursing education in India has experienced significant growth and transformation, positioning itself as a critical driver for the future of global healthcare delivery. The expansion of nursing colleges, standardization of curricula, and the integration of advanced technologies have elevated the competency and global relevance of Indian nurses. This transformation has been driven by the increasing demand for skilled healthcare professionals, particularly in the context of India’s growing economy and aging population. The expansion of nursing colleges, standardization of curricula, and the integration of advanced technologies have elevated the competency and global relevance of Indian nurses. This growth in nursing education has been facilitated by the government’s initiatives to improve healthcare infrastructure and the increasing collaboration between Indian and international institutions. Despite these advancements, challenges such as workforce shortages, educational barriers, and the need for specialized training persist. Addressing these issues through curriculum innovation, policy reform, and international alignment will further strengthen India’s contribution to the global healthcare workforce and ensure the delivery of high-quality, holistic care worldwide.